THE EFFECT OF FINANCIAL LITERACY KNOWLEDGE ON THE FINANCE MANAGEMENT OF FARMERS “SIWALAN” IN EAST JAVA - Rohayat, Suci; Soetjipto, Budi Eko; Haryono, Agung; Wahyono, Hari; Wulandari, Siti Sri (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the influence of financial literacy knowledge on the management of the financial management of Siwalan farmers. Research conducted in Gresik, East Java in Indonesia. Data is collected through questionnaires to respondents, while data is analyzed using T-Test. The findings show that there are several indicators of the knowledge variable of financial literacy which has no effect on the basic knowledge indicator of small Medium business financial management which means that the farmer still thinks that they are able to survive long enough in managing their business without adding or changing business management system. There are also negative indicators and significant that are the SME’s loans and savings on the financial management of the Siwalan farmers. It has the meaning that the weak knowledge of the loan procedure and the savings of small-medium enterprises owned by the Borassus Flabelliform influential people with knowledge of interest rates and credit, weak intake of opportunities or benefits offered by the financial services, unable to explain the financial concept of its business. However, based on the value of R Square it can be concluded that there is a simultaneous influence of the knowledge variable of financial literacy to the financial management variables.